Uso do biospeckle como ferramenta de diagnóstico precoce na avaliação da qualidade de sementes de café - Vivas, Pauliani Gonçalves (2015)
The slow and uneven germination of coffee beans is a major issue in its production, making it difficult to assess quality in time for seed production by means of traditional methods, such as germination. Tests that could reduce the time expended in evaluating the physiological potential of coffee seeds would allow early decision-making during harvesting operations, reception, processing, marketing and seedling production, reducing risks and losses. Thus, the aim of this study was to evaluate the p otential of the biospeckle technique, based on the optical phenomenon of interference, as a tool for evaluating coffee seed viability, comparing the results obtained with the germination and tetrazolium tests. To compare the biospeckle results with the ger mination test, we used five lots with different physiological qualities of Coffea arábica cultivar Mundo Novo coffee seeds. The experiment was conducted in three replicates, with 50 seeds per lot. The soaked seeds were placed in germination chamber at 30°C . At the 6 th day of soaking, we conducted lighting and biospeckle readings. The seeds were placed back into the germinator to complete the germination test until the 30 th day. To compare the results with the tetrazolium assay, we used three seed lots with 4 replicates of 25 seeds per lot. When comparing the results of the biospeckle with the germination and tetrazolium tests, the activity recorded by the biospeckle laser proved to be a good parameter for non-invasive detection of coffee seed quality.